GENERALISASI q-DERIVASI DI BE-ALJABAR - Elsi Fitria; Endah Dwi Jayanti; Sri Gemawati (Universitas Islam Negeri Imam Bonjol Padang, 2023)
BE-algebra is an algebra (X; *,1) of type (2,0) that satisfies the axioms (BE1) x*x=1, (BE2) x*1=1, (BE3) 1*x=x, and (BE4) x*(y*z)=y*(x*z) for all x,y,z ∈X. In this paper, the concept of generalization of q-derivation in BE-algebra is defined and its properties are determined. Then,we discuss the properties of the kernel of a generalized q-derivation in BE-algebra based on their relation to its elements.